Pengaruh Lingkungan Kerja terhadap Disiplin Kerja dan Semangat Kerja Pegawai pada Dinas Perikanan dan Kelautan Provinsi Sumatera Utara - Intan Diana Putri (Universitas Harapan Medan, 2021)
The purpose of this study was to determine and analyze the effect of the work environment on work discipline, the influence of the work environment on work morale and the indirect effect of the work environment on work morale through work discipline at the Department of Fisheries and Maritime Affairs of North Sumatra Province. The method used in this study is a quantitative method with multiple linear regression analysis and sobel. The sample used in this study were 130 employees of the Department of Fisheries and Maritime Affairs of North Sumatra Province. The results of this study indicate that the Work environment has no effect on the Work Discipline of the employees of the Department of Fisheries and Maritime Affairs of North Sumatra Province. The Work Environment has a positive and significant influence on the Work Enthusiasm of the employees of the Department of Fisheries and Maritime Affairs of the Province of North Sumatra and there is an indirect influence between the Work Environment on the Work Enthusiasm through Work Discipline.